Usulan perbaikan sistem kerja express maintenance berdasarkan Kaizen dan simulasi ProModel pada PT Setiajaya Mobilindo Cibubur - Lukman Nurfikri; Asep Endih Nurhidayat; Puji Suharmanto (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
PT Setiajaya Mobilindo Cibubur is an authorized Toyota dealer, in the service division there is Express Maintenance. Express Maintenance (EM) is a special work system for vehicle periodic service maintenance without complaints with a periodic service process for 40 minutes. But in reality there is a problem with the service process time of more than 40 minutes, this is caused by repeated service processes, there are still customer complaints at SPK EM and additional work or part estimates that cause the service lead time to be more than the standard, which is one hour. This study aims to reduce the time of the EM service process to be faster by making suggestions for improvements to the SOP of the EM periodic service process and a ProModel simulation is made to determine the difference between the simulation before and after the repair. On this basis, researchers used kaizen and ProModel. After measuring the standard time before periodic service repairs for 45.6 minutes, repairs are carried out such as kaizen plans by identifying problems using the fishbone, the periodic service process time is not 40 minutes and the corrective steps are given using 5W+1H. Do kaizen implementation based on the plan in the form of periodic service improvement proposals in EM, check sheets and checklists. Check kaizen by measuring the standard time after repair, which is 30.5 minutes. Actions in the form of preventive measures and control tools so that problems do not arise. The result shows that the standard time becomes 30.5 minutes after repair, there is a difference of 10 minutes or 33% from the condition before repair. In addition, the total entries in the ProModel simulation have increased from 209 to 331 units or the EM production capacity has increased by five units/day.